An update regarding the zoonosis of SARs-CoV-2 two years after the pandemic - Iannacone Oliver, José (2022)
In the letter we provide an update regarding the zoonotic role of SARS-CoV-2 (Severe Acute Respiratory Syndrome 2), especially when analyzing the letter entitled: "Current and controversies of zoonosis as the origin of SARS-CoV-2" (Mirror -Sotelo & Tello-Arquiñego, 2021), which analyzes and updates the review article "Zoonotic links of the SARS-CoV-2 coronavirus" (Iannacone et al., 2020). In the aforementioned letter, interesting contributions are mentioned in relation to the theme. However, as of June 2022, controversial conclusions continue to be drawn regarding the issue.